Does the Presence of Micronuclei in Cervicovaginal Smears Help Diagnose Cancer Early? - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The presence of micronuclei is an indicator of chromosomal instability, which may be associated with cancer. Cervical smears, which are commonly used in cervical carcinoma screening, are non-invasive samples of exfoliated epithelial cells, such as buccal mucosa cells.Aims:We aimed to demonstrate the association between micronucleus frequency and cancer if any was present.Settings and Design:This retrospective study was performed in our laboratory. A total of 4500 conventional cervical smears screened in the past 3 years (January 2015–2018) were included in the study.Materials and Methods:Cervical smear samples of 4000 patients, all of cytologic samples, were analysed using light microscopy under oil immersion (×1000) for the determination of micronuclei. The health information of patients with micronuclei was viewed in the hospital information system, and we investigated whether they had malignant tumours.Statistical Analysis Used:The Chi-square test was performed.Results:One hundred and forty-seven patients had micronuclei, and 3853 had none. Malignant tumours were detected in 29 of the 147 patients, no tumour was detected in 118. A statistically significant correlation was found between the presence of micronuclei and the presence of malignant epithelial tumours in the body and in the presence of micronuclei in cervical smears (P< 0.05).Conclusions:We found that the incidence of malignant epithelial tumours was 108.58-fold higher in cases with micronucleus than those without micronucleus. We believe that we can detect both cervical pathologies and epithelial tumours in other organs using the same test and that this finding should be transferred to pathology reports.